JAMPI: A C++ Parallel Programming Interface Allowing the Implementation of Custom and Generic Scheduling Mechanisms - Di Domenico, Daniel; Cavalheiro, Gerson G. H. (Proceedings (Symposium on Computer Architecture and High Performance Computing), 2020)
The widespread of modern parallel architectures brought many challenges in terms of programming. In response, many parallel programming tools intend to aid the user in order to exploit hardware resources effectively. As a new alternative, this paper introduces the design and implementation of JAMPI, a generic parallel programming interface developed in C++ focused on code reuse, productivity and high-level abstraction to enable the construction of parallel applications. JAMPI is totally integrated with its host programming language and offers, as main feature, a fully disassociation of its programming interface from its scheduling mechanism. Aiming to manage and optimize the parallel execution, the proposed interface allows the programmer to implement a custom scheduling heuristic for each portion of the application code. Besides JAMPI model description, we proceeded some preliminary experiments using applications encoded with the proposed framework. Results showed that JAMPI can be used to reach performance on multicore platforms and does not add performance penalty over the sequential version of the benchmarks.